The Effects of Planning on Complexity, Accuracy, and Fluency in Indonesian EFL Learners’ Descriptive Writing - Ika Putri Dekatari (Institut Parahikma Indonesia, 2023)
The study aimed to investigate the effects of planning (pre-task planning (PTP) and on-line planning (OLP)) on the complexity, accuracy, and fluency (CAF) of Indonesian EFL learners’ Descriptive writing. This research involved two undergraduate students whose first language (L1) is Bahasa and English as their second language (L2), majoring at Meteorology in ITB (Bandung Institute of Technology), aged 21 and 25 years old. Their language proficiency level was considered to be upper-intermediate as their TOEFL-PBT scores were above 450. The data were obtained through Descriptive writing tasks and a semi-structured interview through a third party, and they were analyzed using the measured linguistics features. The study revealed that factors such as the age of acquisition of the target language, strategy preferences/planning format (PTP or OLP), along with the time limit and word count affected the participants’ Descriptive text writing performances. This work also showed that both planning formats could assist the participants to produce relatively high-quality texts as participant A seemed to benefit from the pre-writing task because her writing performance was better in the PTP condition than OLP one while participant B appeared to benefit from the OLP format as it allowed her to modify/revise her work freely without time constraint.